2014
DOI: 10.1159/000356656
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Protects Vascular Smooth Muscle Cells From TGF-�1-Stimulated Calcification by Inducing Autophagy via Suppression of the �-Catenin Pathway

Abstract: Background: Arterial calcification is a major event in the progression of atherosclerosis. It is reported that statins exhibit various protective effects against vascular smooth muscle cell (VSMC) inflammation and proliferation in cardiovascular remodeling. Although statins counteract atherosclerosis, the molecular mechanisms of statins on the calcium release from VSMCs have not been clearly elucidated. Methods: Calcium content of VSMCs was measured using enzyme-linked immunosorbent assay (ELISA). The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 42 publications
5
65
0
2
Order By: Relevance
“…HE indicates hematoxylin and eosin; and mTOR, mammalian target of rapamycin. Downloaded from http://ahajournals.org by on September 3, 2018 February 2, 2018 Also, Liu et al 35 demonstrated that atorvastatin attenuates vascular smooth muscle cell calcification by inducing autophagy, which is in good correspondence with our own results on the effects of miR-100 on endothelial autophagy.…”
Section: Discussionsupporting
confidence: 89%
“…HE indicates hematoxylin and eosin; and mTOR, mammalian target of rapamycin. Downloaded from http://ahajournals.org by on September 3, 2018 February 2, 2018 Also, Liu et al 35 demonstrated that atorvastatin attenuates vascular smooth muscle cell calcification by inducing autophagy, which is in good correspondence with our own results on the effects of miR-100 on endothelial autophagy.…”
Section: Discussionsupporting
confidence: 89%
“…Atorvastatin, initially used as a modulator of hypercholesterolemia, has been recently associated with different functions, such as protection against microvascular damage, antifibrotic and anticalcifying effects; in addition, it exhibits antioxidant properties if administered in high doses for the pretreatment of lesions of the myocardium in heart failure, renal disease and abdominal surgery (35)(36)(37). These functions are due to the effect of this drug on populations of mononuclear cells, for example the subpopulations of TCD4 + lymphocytes in reciprocity with or independent from the population of cells of the mononuclear system, such as tissue macrophages, Kupffer cells in the liver, microglial cells in the central nervous system and mucosal dendritic cells (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it worthwhile to mention that statins, such as simvastatin and atorvastatin, have pleiotropic effects, including the induction of autophagy, that are well beyond their lipid-lowering properties. 110,111 For other autophagy-inducing drugs, a link between autophagy induction and the prevention (or amelioration) of vascular disease is less obvious. For example, resveratrol is a polyphenol present in red wine that attenuates endothelial inflammation by inducing autophagy in an mTOR-independent way via several key molecules, including cAMP, AMPK, and sirtuin 1.…”
Section: Systemic Administration Of Rapamycin and Rapalogsmentioning
confidence: 99%